Mouse hepatitis virus infection upregulates genes involved in innate immune responses. - Dhriti Chatterjee; Sankar Addya; Reas S Khan; Lawrence C Kenyon; Alexander Choe; Randall J Cohrs; Kenneth S Shindler; Jayasri Das Sarma (PLoS ONE, 2014)
Neurotropic recombinant strain of Mouse Hepatitis Virus, RSA59, induces meningo-encephalitis, myelitis and demyelination following intracranial inoculation. RSA59 induced neuropathology is partially caused by activation of CNS resident microglia, as demonstrated by changes in cellular morphology and increased expression of a microglia/macrophage specific calcium ion binding factor, Iba1. Affymetrix Microarray analysis for mRNA expression data reveals expression of inflammatory mediators that are known to be released by activated microglia. Microglia-specific cell surface molecules, including CD11b, CD74, CD52 and CD68, are significantly upregulated in contrast to CD4, CD8 and CD19. Protein analysis of spinal cord extracts taken from mice 6 days post-inoculation, the time of peak inflammation, reveals robust expression of IFN-γ, IL-12 and mKC. Data suggest that activated microglia and inflammatory mediators contribute to a local CNS microenvironment that regulates viral replication and IFN-γ production during the acute phase of infection, which in turn can cause phagolysosome maturation and phagocytosis of the myelin sheath, leading to demyelination.